Exploring changes in dietary intake, physical activity and body weight during chemotherapy in women with breast cancer: A Mixed‐Methods Study. Issue 3 (7th January 2021) - de Kruif, Anja JThCM; Westerman, Marjan J.; Winkels, Renate M.; Koster, Marije S.; van der Staaij, Irene M.; van den Berg, Maaike M. G. A.; de Vries, Jeanne H. M.; de Boer, Michiel R.; Kampman, Ellen; Visser, Marjolein
Abstract: Background: The present study aimed (i) to assess changes in dietary intake (DI), physical activity (PA) and body weight (BW) in breast cancer patients during chemotherapy; (ii) to describe how women explained, experienced and dealt with these potential changes; and (iii) to eventually develop lifestyle intervention strategies tailored to the women's personal needs during chemotherapy. Methods: A longitudinal parallel mixed‐method design was used with quantitative assessment of changes in dietary intake (24‐h recall, Appetite, Hunger, Sensory Perception questionnaire), physical activity (Short Questionnaire to Assess Health‐enhancing physical activity, Multidimensional Fatigue Inventory) and BW (dual‐energy X‐ray absorptiometry), in addition to qualitative interviews with 25 women about these potential changes during chemotherapy. Results: Most women who perceived eating less healthily with low energy intake (EI) and being less active before diagnosis continued to do so during chemotherapy, according to quantitative measurements. They struggled to maintain sufficient energy intake. Despite a lower than average reported EI, they unexpectedly gained weight and explained that fatigue made them even more inactive during chemotherapy. Active women usually managed to stay active because exercise was very important to them and made them feel good, although they also suffered from the side‐effects of chemotherapy. They found more ways to deal with taste, smell and appetite problems than women with a lower energy intake. Conclusions: The combination of the quantitative and qualitative data provided more insight into the changes in dietary intake, physical activity and BW during chemotherapy. The women's explanations showed why some women remain active and others need support to deal with changes in lifestyle factors such as healthy nutrition and fatigue. Abstract : In this longitudinal mixed‐method study, we quantitatively assessed changes in diet, physical activity and body weight, and qualitatively assessed how individual women with breast cancer experienced, explained, and responded to these changes during chemotherapy, enriching and clarifying the quantitative data. The findings showed that some women remained active with fewer dietary problems, while others struggled with adequate food intake, opportunities to be active, and experienced unexpected weight gain. Women with breast cancer need support to be active and to cope with fatigue, and they need help with their eating habits to develop lifestyle intervention strategies tailored to their personal needs during chemotherapy.